Retraction: Investigation on corrosion protection and mechanical performance of minerals substituted hydroxyapatite coating on HELCDEB-treated titanium using pulsed electrodeposition method. Issue 15 (29th March 2023) - Gopi, D.; Karthika, A.; Rajeswari, D.; Kavitha, L.; Pramod, R.; Dwivedi, Jishnu
Abstract : Retraction of 'Investigation on corrosion protection and mechanical performance of minerals substituted hydroxyapatite coating on HELCDEB-treated titanium using pulsed electrodeposition method' by D. Gopi et al., RSC Adv., 2014, 4, 34751–34759. DOI: ; https://doi.org/10.1039/C4RA04484C .